Novel Technique of Gap Waveguide Cavity Resonator Sensor with High Resolution for Liquid Detection - Ammar Alhegazi; Zahriladha Zakaria; Noor Azwan Shairi; Muhammad Ramlee Kamarudin; Rammah A. Alahnomi; AzieanMohd Azize; Wan Haszerila Wan Hassan; AmyrulAzuanMohd Bahar; Ahmed Jamal Abdullah Al-Gburi (International Journal of Antennas and Propagation)
This article proposes a novel microfluidic sensor designed with a highly accurate Q-factor for liquid detection. The proposed sensor is developed and implemented with a gap waveguide cavity resonator (GWCR) approach. The GWCR approach is formed from the two metallic plates denoted as upper and lower plates. These plates are separated by an array of metallic pins attached to the lower plate, leading to high electric field concentration. A microfluidic channel is created at the midpoint of each plate to place the holder of liquid under test (LUT). The GWCR provides a high electric field, which increases Q-factor and is shown to exhibit a significant improvement in sensitivity and linearity. To characterise and evaluate the dielectric properties of the fluid, the LUT is placed inside a hairlike glass, which passes through the microfluidic channels. The LUT perturbs the electric field distribution inside the GWCR, known as the perturbation principle. The relation between the LUT and the electric field changes the electric field behaviours in terms of resonant frequency, Q-factor, and transmission coefficient. The analysis of these changes in the electric field behaviours leads to identifying the dielectric properties of the LUT. The anonymous dielectric characteristics of LUT, permittivity, and loss tangent formulas are derived utilising the polynomial fitting approach. The measurement outcomes reveal that the stated sensor can measure the permittivity and loss tangent for both LUT samples, such as ethanol and methanol, at 6.1 GHz and 23.4°C.